Fatigue Testing of Weldments 1978
DOI: 10.1520/stp33394s
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Propagation in Aluminum-Zinc-Magnesium Alloy Fillet-Welded Joints

Abstract: The fatigue behavior of aluminum-zinc-magnesium (Al-Zn-Mg) alloy fillet-welded joints was analyzed in fracture mechanics terms. Basic crack propagation data were obtained with −2 ⩽ R ⩽ + 0.5 and correlated using formulas in the literature and, more successfully, in terms of ΔKeff, based on the results of crack closure experiments. The form of the da/dN versus ΔK relationship was influenced by the specimen geometry. A fracture mechanics analysis of the fatigue life of Al-Zn-Mg alloy fillet welds based on the da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1987
1987
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 1 publication
0
8
0
1
Order By: Relevance
“…Die Rückrechnung auf kleine fiktive Anfangsrisse nach der Rißfortschrittsgleichung unter Verwendung von DK-Werten, wie sie von Maddox [1707][1708][1709] oder Hobbacher [1700,1701] für Schweißverbindungen vorgeschlagen wurde, muß dagegen als weniger geeignet angesehen werden, weil sie dem tatsächlichen Kurzrißfortschrittsverhalten auch nicht näherungsweise entspricht.…”
Section: Rückrechnung Auf Fiktive Anfangsrißgrößeunclassified
“…Die Rückrechnung auf kleine fiktive Anfangsrisse nach der Rißfortschrittsgleichung unter Verwendung von DK-Werten, wie sie von Maddox [1707][1708][1709] oder Hobbacher [1700,1701] für Schweißverbindungen vorgeschlagen wurde, muß dagegen als weniger geeignet angesehen werden, weil sie dem tatsächlichen Kurzrißfortschrittsverhalten auch nicht näherungsweise entspricht.…”
Section: Rückrechnung Auf Fiktive Anfangsrißgrößeunclassified
“…Large databases of test results have been used to establish the current fatigue design provisions for aluminum welds. Fatigue test results on specific weld details have been reported in several studies (Maddox and Webber 1977;Maddox 1995;Mazzolani and Grillo 1995). Others have compiled test results and discussed the development of the current fatigue design provisions (Menzemer and Fisher 1995;Jaccard et al 1995;Soetens et al 1995;Maddox 2003), which commonly employ fatigue-resistance (S-N) curves and the detail category approach.…”
Section: Introductionmentioning
confidence: 74%
“…21) Recent work has shown that the thickness effect depends on the overall proportions of the welded joint. 22,23) The fatigue rules in Eurocode 9 accounts for this effect. A further refinement in the IIW recommendations modifies the thickness correction exponent p for various welds.…”
Section: Size Effectmentioning
confidence: 99%